The Optimal Placement of Shutoff Rods in CANDU Nuclear Reactors (Part A) - Gordon, Charles W. (My University, 1975)
The optimal placement of shutdown systems in power reactors is investigated, in particular, the placement of mechanical and liquid shutoff rods. Two CANDU reactor cores were used as a basis for evaluation. The optimal shutdown system was defined here to be one which, with the least number of rods, maximizes the reactivity depth of the system with the two most effective rods assumed to be absent. It was found that rows of rods placed parallel to the fuel channels were more effective and four of these rows were required in a simple core. For real cores where positions are limited six or seven rows were needed to obtain a large system worth. (Time analysis was not done to evaluate insertion rate and delay effects on the power transient in the case of an accident.)
Keywords: CANDU, optimal, power reactors, rods, reactivity